2018
DOI: 10.21608/smj.2018.34692
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyl-L-Cysteine ameliorates oxidative stress and reproductive toxicity induced by nicotine in male rats

Abstract: Background: The current study assessed the protective role of N-acetyl-L-Cysteine in alleviating the detrimental effect of nicotine on reproductive functions in male rats. Methods: twenty four adult male albino rats were divided into four groups of six rats. Control group was treated orally with 0.5ml/kg normal saline, nicotine treated group received 1.0 mg/kg of nicotine i.p, N-acetyl-L-Cysteine treated group received 100 mg/kg and 200 mg/kg i.p for four weeks. Results: Nicotine caused significant reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…NAC, in combination with sodium bicarbonate [104] or atropine Shadnia [105] was also advised for treating humans to alleviate the negative effects of OPs, such as shortening hospital stays. In line with Abouelella, et al [106] who cited that, NAC reduces nicotine-induced oxidative stress and reproductive damage in male rats.…”
Section: Discussionsupporting
confidence: 83%
“…NAC, in combination with sodium bicarbonate [104] or atropine Shadnia [105] was also advised for treating humans to alleviate the negative effects of OPs, such as shortening hospital stays. In line with Abouelella, et al [106] who cited that, NAC reduces nicotine-induced oxidative stress and reproductive damage in male rats.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly in rat brain tissue, NAC therapy exhibits antioxidant, anti-inflammatory, and anti-apoptotic properties against chlorpyrifosinduced neurotoxicity (Mahmoud et al, 2019). According to Abouelella et al (2018), NAC saves the reproductive system by reducing nicotine-induced oxidative stress and reproductive injury in male rats. Furthermore, Kheradmandi et al (2019) found that injecting NAC intraperitoneally with chlorpyrifos reduces the pesticide's negative effects on mice testis.…”
Section: Discussionmentioning
confidence: 99%